An ANALYSIS OF GRAMMAR ERROR IN PUBLIC SPEECH PROGRAM AT GENTA ENGLISH COURSE IN GENDONG LAREN-LAMONGAN - Suhartono Suhartono; Sutardi Sutardi; Khoirul Huda (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
Many students who did not confident with their speaking ability when they want to speak in front of the audience so Public speaking is a program that is suitable to improve their speaking ability. This study was aimed to know whether Genta’s program (Public Speech) all speakers did the errors on grammar at public speaking Genta English Course or not. The research described that are (a) what are errors on grammar at public speaking. (b) What are the causes of errors on grammar at public speaking? Especially about: analysis of errors on Grammar. This study is descriptive qualitative on analyzing errors. The subjects of this study were the students of Genta English Course in Gendong – Laren - Lamongan. The instruments used in this study were observation form, interview guide, and documentation. The data collected from observation and interview was analyzed based on analyzing, the researcher manages the series data and it involve identification, classifying, presenting and conclusion. The result of this study described that all the speakers did errors on grammar at public speech exactly at sentence and phrase because of the speakers less understand of the structure of grammar. In analyzing of errors on grammar at public speech here, the research gave contribution and show that the data, correct, and the solution. When the speakers did the errors on grammar at public speech, it happened in present tenses, part of speech, modal, degree of comparison and passive. And this result can be presented in present tense 28.6%, part of speech 53.6%, and modal 10.7%, degree of comparison 3.6% and passive 3.6%. it had discussed by the researcher. It was found value of analyzing this result then discussed on grammar at public speech so all speakers did not do the errors any more on grammar at public speech Genta English Course in Gendong.